RESEÑA de : Alzaga Villaamil, Óscar. Del consenso constituyente al conflicto permanente. Madrid : Editorial Trotta, Fundación Alfonso Martín Escudero S.A., 2011 - Diego Arias, Juan Luis de (Revista de Derecho de la UNED (RDUNED), 2011)
-